The Value of Bosses - Lazear, Edward P.; Shaw, Kathryn L.; Stanton, Christopher T. (Journal of Labor Economics, 2015)
How and by how much do supervisors enhance worker productivity? Using a company-based data set on the productivity of technology-based services workers, we estimate supervisor effects and find them to be large. Replacing a boss who is in the lower 10% of boss quality with one who is in the upper 10% of boss quality increases a team’s total output by more than adding one worker to a nine-member team would. Workers assigned to better bosses are less likely to leave the firm. A separate normalization implies that the average boss is about 1.75 times as productive as the average worker.